Refining the care of patients with pancreatic cancer: the AGITG Pancreatic Cancer Workshop consensus. Issue 11 (20th June 2016) - Gandy, Robert C; Barbour, Andrew P; Samra, Jaswinder; Nikfarjam, Mehrdad; Haghighi, Koroush; Kench, James G; Saxena, Payal; Goldstein, David
Summary: A meeting of the Australasian Gastro‐Intestinal Trials Group (AGITG) was held to develop a consensus statement defining when a patient with pancreatic cancer has disease that is clearly operable, is borderline, or is locally advanced/inoperable. Key issues included the need for multidisciplinary team consensus for all patients considered for surgical resection. Staging investigations, to be completed within 4 weeks of presentation, should include pancreatic protocol computed tomography, endoscopic ultrasound, and, when possible, biopsy. Given marked differences in outcomes, the operability of tumours should be clearly identified by categories: those clearly resectable by standard means (group 1a), those requiring vascular resection but which are clearly operable (group 1b), and those of borderline operability requiring vascular resection (groups 2a and 2b). Patients who may require vascular reconstruction should be referred, before exploration, to a specialist unit. All patients should have a structured pathology report with standardised reporting of all seven surgical margins, which identifies an R0 (no tumour cells within a defined distance of the margin) if all surgical margins are clear from 1 mm. Neo‐adjuvant therapy is increasingly recommended for borderline operable disease, while chemotherapy is recommended as initial therapy for patients with unresectable loco‐regional pancreatic cancer. The value of adding radiation after initial chemotherapy remains uncertain. A small number of patients may be downstaged by chemoradiation, and trimodality therapy should only be considered as part of a clinical trial. Instituting these recommendations nationally will be an integral part of the process of improving quality of care and reducing geographic variation between centres in outcomes for patients.